Resistensi Wereng Cokelat terhadap Insektisida yang Beredar di Sentra Produksi Padi - E., Baehaki S.; Iswanto, E. H.; Munawar, D. (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Research on brown planthopper (BPH), (Nilaparvata lugens (Stal.) resistant to insecticide using dipping method was carried out in the wet season (WS) of 2011/2012 at Indonesian Center for Rice Research, Sukamandi. BPH field population from Sukamandi, West Java, known as Sukamandi BPH population and Juwiring, Central Java, as Juwiring BPH population, were measured their degree of resistance to insecticides to be compared with the BPH biotype 1 of screen house population. The insecticides used were imidacloprid, ethiprole, thiamethoxam, fipronil, BPMC, MIPC, buprofezin, cypermethrin and cyhalothrin. The resistance ratios (RR) were measured by LC50 of BPH from fields/LC50 of BPH from screen house. Results showed that Sukamandi BPH population was moderately resistance to imidacloprid and cypermethrin, but was low resistance to buprofezin, and was decreasing into susceptibility to fipronil, thiamethoxam and cyhalothrin, where as to ethiprole, BPMC dan MIPC the Sukamandi BPH was still susceptible. The Juwiring BPH population was low resistance to imidacloprid, buprofezin, cypermethrin and cyhalothrin, but the Juwiring BPH was decreasing into susceptibility to BPMC, ethiprole and fipronil. The population was still susceptible to thiamethoxam and MIPC.